Green material procurement implementation towards green buildings / Shahela Mamter ... [et al.] - Shahela, Mamter; Siti Rohayu, Jusoh; Mohd Esham, Mamat; Norazlin, Mat Salleh (2015)
Nowadays, construction industry has increasingly demanding and important in Malaysia. However, the current practices of the construction industry have significant impacts on environment. In order to minimize the issues on the environment, green buildings have been implemented in Malaysia. On the other hand, to ensure that the buildings are certified as green building, green materials must be used to environmental friendly.. Hence, the aim of this research is to investigate the green material procurement awareness among contractors towards the implementation of green building. These paper objectives are to identify the implementation of green material procurement in Malaysia and to examine the barriers and challenges for implementation of green material procurement faced by contractors. A total numbers of 95 questionnaires were distributed to G7 and G6 contractors in Selangor. Only 57 questionnaires were returned and were analyzed using Statistical Package for Social Science (SPSS) version 21.0 software. The researcher revealed that the most of the contractors are aware and getting serious attention but still in infancy stage to use green material procurement towards the implementation of green building. Many recommendations were analyzed by researcher in order to sustain the implementation of green material procurement in Malaysia.